Penggunaan Metode Flaschcard Interaktif untuk Edukasi Kesehatan Gigi pada Anak di MIN-Lingga - Anas, Siti Nafiah; Herniwanti , Herniwanti; Ningrum, Hesti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This study aimed to improve dental health awareness and hygiene practices among children aged 8–10 years at MIN Lingga through the use of interactive flashcard-based education. The intervention was designed to address the high prevalence of dental caries and the limited preventive programs in schools. Research methodology: A community service approach was employed, involving 120 students from grades 3 to 5. The program consisted of health education sessions using visual media (flashcards), tooth brushing demonstrations, and supervised group brushing practices. The sessions included active participation from teachers and parents to reinforce learning outcomes and ensure behavior adoption at home. Results: Post-intervention observations revealed significant improvements in the students’ understanding of and practices regarding oral hygiene. The use of visual aids, such as flashcards, increased engagement, and parental involvement enhanced the continuity of healthy habits at home. Conclusions: The interactive flashcard program at MIN Lingga effectively improved students’ oral hygiene knowledge and habits, reduced dental caries prevalence, and demonstrated that visual collaborative education involving teachers and parents fosters sustainable health behavior in children. Limitations: This program was limited to one school with a specific age range (8–10 years) and did not include long-term follow-up to assess the sustainability of behavioral change. Contribution: This study provides a replicable model for integrating interactive visual media and stakeholder collaboration into school-based dental health programs. It highlights the importance of parental involvement and teacher facilitation in reinforcing hygiene education, making it a scalable intervention for similar public health initiatives.